Simulation and Experimental Study of Arc Model in a Low-Voltage Distribution Network - Binbin Zhang; Jiaqing Zhang; Yifeng Cheng; Qixu Chen; Qian Zhang (Energies)
Using the low-voltage and low-current platform (220 VAC-10 A), this paper selected the Mayr arc theoretical model and the improved control theory model as a theoretical basis and built a single-phase low-voltage AC series arc model based on Simulink. The simulation results showed that arc dissipation power directly determined arc voltage amplitude, arc time constant influenced arc voltage waveform, and arc current was mainly determined by load resistance. Because the arc length parameter can be set by the improved control arc theory model, the arc can be drawn only at the micro-distance of two electrodes, which is more suitable for describing the arc characteristics of low voltage and low current. A scheme of large ratio reducer for permanent magnet brushless DC motor was developed, which was combined with the stepless governor controlled by PWM and the positive and negative switch to realize the adjustment of the two-electrode micro-distance. The collection and analysis of arc voltage and arc current under pure resistance, resistive load, and multi-branch load were completed. The experimental results also verified that the Mayr arc and improved control theory arc have good accuracy in describing low voltage and low current characteristics, which improves data support for later fault identification and removal.